The Effect of Oral Doses of Chitosan-Titanium Nanoparticles on Some Physiological Parameters of Male Albino Rats Infected with Acrylamide - Hamoud , Maha Khalil; Muhammed, Muhammed Jamil; Badawi , Amin Suleiman (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
The study aimed to determine the characteristics of nanoparticles, such as shape, size, aggregates, absorption using appropriate equipment, and determine the effect of dosing with chitosan-titanium nanoparticles on some physiological parameters of male rats exposed to acrylamide. We notice a significant decrease in the total number of red blood cells, hemoglobin, the percentage of red blood cells, the number of platelets, lymphocytes, and HDL in the group of rats exposed to acrylamide compared with the healthy control group, as well as a significant increase in the values of white blood cells, monocytes, cholesterol, triglycerides, and LDL. and VLDL compared with the control group. ((While we notice, when adding nanoparticles with acrylamide, a significant increase in the total number of red blood cells, hemoglobin, the percentage of red blood cells, the number of platelets, lymphocytes, and HDL. We also notice a decrease in the numbers of WBC, monocytes, cholesterol, TG, LDL, and VLDL compared to the group exposed to acrylamide.)) While we notice that when nanoparticles are added with acrylamide, there is a significant increase in the total number of red blood cells, hemoglobin, the percentage of red blood cells, the number of platelets, lymphocytes, and HDL, as they were 6.16, 12.00, 45.00, 640.00, 31.00, 37.15, respectively, compared to the group. exposed to acrylamide, which were 4.73, 9.65, 38.50, 588.50, 25.60, 32.65, respectively. We also note a decrease in the numbers of WBC, monocytes, cholesterol, TG, LDL, and VLDL, as they were 6.10, 7.90, 158.75, 99.75, 101.65, and 19.95 compared to those exposed to acrylamide. The group exposed to acrylamide, which was 7.67, 14.95, 197.60, 171.29, 130.68, 34.26, respectively.